O valor percebido pelo consumidor: proposição e teste de um modelo de avaliação no mercado de refrigerantes - Bezerra, Francineide de Morais (2005)
This essay focus on the development and implementation of a model to evaluate consumer perceived value. Initially, it’s discussed the perceived value concept, its importance under strategy and marketing perspectives and its relation to price and quality. The model is presented, considering each step to be followed: perceived quality study of brands in the market; consumer’s perceptions of competitor’s prices; and the value map development, defined considering the relation quality/price for each brand in the market. The model applicability was tested in a soft drink category study in Fortaleza market, based in a survey with 400 consumers. The application shows that the model, built under consumer’s point of view, can provide a descriptive panel of competitor’s positions and relevant information to be used in market diagnoses. The information and the descriptive panel mentioned can be useful, not only in strategic analyses, but also in price formulations.